Management Responsibility And Business Performance Between ISO 9000 And Non-ISO 9000 Certified Contractors In Malaysia. - Said, Ilias; Abidin, Nazirah Zainul; Mohd Shafiei, Dr.Mohd Wira (2006)
The construction industry is classified as one of the sectors that significantly contribute to the Gross Domestic Product (GDP) of a country.